TEACHING STUDENTSâ€™ ENGLISH PRONUNCIATION THROUGH DRAMA TECHNIQUE - Putri, Retno Tamia; Marbun, Rismaya; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : The purpose of this research is to answer the question: Â Â â€œHow is the effectiveness of Drama Technique in teaching pronunciation especially the sounds /t/, /d/, /Î¸/, /Ã°/and /r/?â€ The method of this research is pre-experimental research. The sample of this research was is students of Teacher Training and Education Faculty English Study Program Tanjungpura University Reguler B class A which consists of 25 students.Â The treatments were given three times in order to know the effectiveness of teaching English pronunciation through Drama Technique. The technique of data collecting was reading test; some dialogues that were consisted of certain sounds that was being researched from a nativeâ€™s drama. The research finding showed that the total score of studentsâ€™ pre-test is 1747 and the total score of studentsâ€™ posttest is 1888. The studentsâ€™ total score in posttest is higher than the total score of studentsâ€™ posttest. The result of effect size of treatment was 0.994. According to the criteria of effect size 0.994 is concluded as moderate effect. Keyword : Pronunciaton, Drama Technique, Pre Experimental Â Abstrak : Tujuan dari penelitian ini adalah untuk menjawab pertanyaan : â€œSeberapa efektif teknik drama dalam pengajaran pengucapan khsusunya bunyi /t/, /d/, /Î¸/, /Ã°/and /r/?â€ Metode penelitian yang digunakan dalam penelitian ini adalah pre-ekperimental. Sampel yang diamati dalam penelitian ini adalah mahasiswa Fakultas Kegurusan dan Ilmu Pendidikan di Universitas Tanjungpura Reguler B Kelas A yang terdiri dari 25 siswa. Treatment diberikan sebanyak tiga kali. Teknik yang digunakan untuk mengumpulkan data adalah tes membaca; beberapa dialog yang diambil dari naskah drama native. Hasil dari penelitian menunjukkan data bahwa skor rata-rata pretest adalah 1747 dan data skor rata-rata posttest adalah 1888. Nilai rata-rata post-test lebih tinggi daripada hasil rata-rata nilai pre-test. Â Hasil akhir effect size adalah 0.994. Berdasarkan kriteria effect size, 0,994 termasuk efek sedang. Kata kunci : Pengucapan, Teknik Drama, Pre Eksperimental